2008
DOI: 10.1007/s00015-008-1248-2
|View full text |Cite
|
Sign up to set email alerts
|

The Grenchenberg conundrum in the Swiss Jura: a case for the centenary of the thin-skin décollement nappe model (Buxtorf 1907)

Abstract: When Buxtorf in 1907 proposed his décollement hypothesis which visualized the Jura fold belt as a "folded décollement nappe" pushed by the Alps, he met with both fervent support of a few and skepticism by the many. As an illustration of recalcitrant problems within the Jura décollement nappe, that remain after 100 years, a model of the Grenchenberg complex is presented within the frame of 3D décollement kinematics, based on a set of rules gleaned from recurrent features in the Jura: (1) that generally progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These differences stress the need for a separate examination of each domain and show that structural studies in the Eastern Jura may not apply to the Central Jura. Previous studies in the Eastern Jura are found in Laubscher (1986), Bitterli (1992), Noack (1995) and Laubscher (2008), and additionally in reports of the National Cooperative for the Disposal of Radioactive Waste (Nagra). The Central and Western Jura Mountains were extensively studied by Philippe (1995), Sommaruga (1997) and Affolter (2003).…”
Section: Geological Settingmentioning
confidence: 91%
See 1 more Smart Citation
“…These differences stress the need for a separate examination of each domain and show that structural studies in the Eastern Jura may not apply to the Central Jura. Previous studies in the Eastern Jura are found in Laubscher (1986), Bitterli (1992), Noack (1995) and Laubscher (2008), and additionally in reports of the National Cooperative for the Disposal of Radioactive Waste (Nagra). The Central and Western Jura Mountains were extensively studied by Philippe (1995), Sommaruga (1997) and Affolter (2003).…”
Section: Geological Settingmentioning
confidence: 91%
“…The applied forward modelling technique grants a wide degree of freedom owing to its non-physical nature and therefore it is crucial to make use of a default structural style (Laubscher 2003(Laubscher , 2008, defined by assumptions and observations with a physical background. Here the default structural style is defined as follows: (1) the folds of the Haute-Chaîne were initiated with a detachment in the Triassic anhydrites and they developed into fault-propagation and fault-bend folds after the outbreak of thrusts (Sommaruga 1999).…”
Section: Default Structural Stylementioning
confidence: 99%
“…It presumably follows an inherited Paleozoic structure and has been repeatedly reactivated in Mesozoic times and during rifting of the Rhine Graben in the Oligocene [ Allenbach and Wetzel , ]. During the late Miocene main deformation phase in the Jura fold‐and‐thrust belt [ Becker , ], inherited structures related to the Rhenish Lineament have been reactivated in a left‐lateral strike‐slip manner, while at the same time they were transported 10–12 km to the NNW [ Laubscher , , ]. Seismicity shows present‐day activity of the SFZ‐Rhenish Lineament system (Figure ).…”
Section: Discussionmentioning
confidence: 99%